Brain Structure and Function Changes During the Development of Schizophrenia: The Evidence From Studies of Subjects at Increased Genetic Risk - Lawrie, Stephen M. (Oxford University Press, 2008)
This article reviews the evidence for changes in the structure and function of the brain in subjects at high risk of schizophrenia for genetic reasons during the genesis of the disorder. We first highlight the structural and functional abnormalities in schizophrenia and whether any similar or lesser abnormalities are apparent in unaffected relatives. There is good evidence for subtle abnormalities of hippocampal and ventricle volume in relatives that are not as marked as the deficits in schizophrenia. In addition, the functional imaging literature suggests that prefrontal cortex function may deteriorate in those at risk who go on to develop the disorder. We then review the findings from longitudinal imaging studies of those at high risk, particularly the Edinburgh High-Risk Study, which report gray matter density reductions in medial and lateral temporal lobe because people develop schizophrenia, as well as functional abnormalities which precede onset. We conclude by quoting our own and others’ imaging studies of the associations of genetic and other risk factors for schizophrenia, including stressful life events and cannabis use, which provide mechanistic examples of how these changes may be brought about. Overall, the literature supports the view that there are measurable changes in brain structure and function during the genesis of the disorder, which provide opportunities for early detection and intervention.